Sharp Decrease of Reported Occupational Blood and Body Fluid Exposures in French Hospitals, 2003–2012: Results of the French National Network Survey, AES-RAISIN. (21st April 2015) - Floret, N.; Ali-Brandmeyer, O.; L'Hériteau, F.; Bervas, C.; Barquins-Guichard, S.; Pelissier, G.; Abiteboul, D.; Parneix, P.; Bouvet, E.; Rabaud, C.; Working Group AES-RAISIN
<x content-type="archive" xml:space="preserve">Abstract</x> OBJECTIVE To assess the temporal trend of reported occupational blood and body fluid exposures (BBFE) in French healthcare facilities. METHOD Retrospective follow-up of reported BBFE in French healthcare facilities on a voluntary basis from 2003 to 2012 with a focus on those enrolled every year from 2008 to 2012 (stable cohort 2008–12). FINDINGS Reported BBFE incidence rate per 100 beds decreased from 7.5% in 2003 to 6.3% in 2012 (minus 16%). Percutaneous injuries were the most frequent reported BBFE (84.0% in 2003 and 79.1% in 2012). Compliance with glove use (59.1% in 2003 to 67.0% in 2012) and sharps-disposal container accessibility (68.1% in 2003 to 73.4% in 2012) have both increased. A significant drop in preventable BBFE was observed (48.3% in 2003 to 30.9% in 2012). Finally, the use of safety-engineered devices increased from 2008 to 2012. CONCLUSION Of the 415, 209 hospital beds in France, 26, 158 BBFE could have occurred in France in 2012, compared with 35, 364 BBFE in 2003. Healthcare personnel safety has been sharply improved during the past 10 years in France. Infect. Control Hosp. Epidemiol. 2015;36(8):963–968